A Review on Effects of Exercises Therapy for Office Workers with Chronic No Specific Low Back Pain - Sulaiman, Habibu Muhammad; Shahidu Zafar, Professor (Clinical Medicine And Health Research Journal, 2023)
Study Design: A literature review was conducted in order to provide an overview of the effect of exercise therapy for office workers with chronic Non-specific low back pain. Review provides a summary of large bodies of evidence and reviews help to explain differences among studies. Objectives: The aim of this study is to review exercises therapy for office workers with chronic nonspecific low back pain treatment. Background: Low back pain is a common syndrome that causes disability and absence from work. Although there are several causes, the most common type of back pain is nonspecific. Exercises are often used to treat back pain, but there is controversy regarding its effectiveness. Exercise therapy is widely used as an intervention in low back pain. Low back pain is defined as discomfort that develops above the posterior glutelines and below the costal edge of the final ribs, with or without lower limb pain(1).Between 60 and 85% of people experience it at some point throughout their lives(2). Methods: Search strategy: Relevant articles were identified by engines such as SCIENCE DIRECT, PUBMED, GOOGLESCHOLAR, and COCHRANE DATA BASE OF SYSTEMATIC REVIEW (www.cochrane.org), and CINALE.Website like physiopedia (www.physiopedia.com) was searched and published texts were `also reviewed in these studies.